2021
DOI: 10.1038/s41419-020-03354-4
|View full text |Cite
|
Sign up to set email alerts
|

KDM6B is an androgen regulated gene and plays oncogenic roles by demethylating H3K27me3 at cyclin D1 promoter in prostate cancer

Abstract: Lysine (K)-specific demethylase 6B (KDM6B), a stress-inducible H3K27me3 demethylase, plays oncogenic or antitumoral roles in malignant tumors depending on the type of tumor cell. However, how this histone modifier affects the progression of prostate cancer (PCa) is still unknown. Here we analyzed sequenced gene expression data and tissue microarray to explore the expression features and prognostic value of KDM6B in PCa. Further, we performed in vitro cell biological experiments and in vivo nude mouse models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…As a result of decreased c-MYC, that observed decrease in total cell number is mainly due to decreased proliferation rather than elevated cell death by GSK-J4 in LNCaP cells. To our knowledge, in consistent with our data inhibitory effect of GSK-J4 on PCa cell proliferation has been determined by limited number of studies (Cao et al, 2021;Morozov et al, 2017) but this is the first study, which shows the mechanism of KDM6s controlling proliferation of LNCaP cells via identifying KDM6B downstream targets c-MYC, CCND1 and pRb.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As a result of decreased c-MYC, that observed decrease in total cell number is mainly due to decreased proliferation rather than elevated cell death by GSK-J4 in LNCaP cells. To our knowledge, in consistent with our data inhibitory effect of GSK-J4 on PCa cell proliferation has been determined by limited number of studies (Cao et al, 2021;Morozov et al, 2017) but this is the first study, which shows the mechanism of KDM6s controlling proliferation of LNCaP cells via identifying KDM6B downstream targets c-MYC, CCND1 and pRb.…”
Section: Discussionsupporting
confidence: 88%
“…was found to be regulated by KDM6B in a direct manner via H3K27me 3 demethylase activity in PC3 cells, which was linked to progression of PCa (Cao et al, 2021). Although CCND1 is a known c-MYC target gene, c-MYC controlling CCND1 expression was reported as controversial due to stimulatory (Daksis et al, 1994;Perez-Roger et al, 1999;Yu et al, 2005) or repressive (Philipp et al, 1994;Solomon et al, 1995) effects of c-MYC on CCND1, which seems to depend on specific stimuli and cell type.…”
Section: Discussionmentioning
confidence: 98%
“…Although JMJD3 via epigenetic modifications targets several signaling pathways, off-target effects could lead to minimize the applications of this enzyme in cancer. For example, JMJD3 by promoting cyclin D1 transcription is involved in the development of cancer cells [ 108 ]. Also, JMJD3 can impact other histone modifiers and alter chromatin structure, activate the expression of oncogenes, and trigger the development of many types of human diseases [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, JMJD3 by promoting cyclin D1 transcription is involved in the development of cancer cells [ 108 ]. Also, JMJD3 can impact other histone modifiers and alter chromatin structure, activate the expression of oncogenes, and trigger the development of many types of human diseases [ 108 ]. Thus, further studies are required to determine the downstream targets of JMJD3 in pluripotent and multipotent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of cyclin D1 expression drives uncontrolled cell proliferation and results in the development of human cancers. It has been reported that the expression level of cyclin D1 was markedly upregulated in human PCa, breast cancer, non-small cell lung cancer and hepatocellular carcinoma [ 13 16 ]. Several studies have shown that cyclin D1 expression could be negatively regulated by miR-195 to affect the tumorigenicity and invasiveness of laryngeal squamous cell carcinoma and glioblastoma cells [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%